Addition Urea of syhintesized Zr-BDC with Solvhothermal method - Fitria Wahyu Kurniawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2016)
Benzendikarboksilat - zirconium ( Zr - BDC ) and urea - zirconium - benzendikarboksilat ( U - Zr - BDC ) BDC with variations mmol / Urea = 0.75 ; 1 ; 1.5 ; and 3 successfully synthesized via methods solvotermal . Sample U - Zr - BDC modified characterized by XRD , FTIR and SEM - EDX . Diffractogram at all synthesized showed characteristic peaks at 2θ = 7.4 and 8.5 with a different intensity . FTIR analysis showed the presence of wave number at 1100 cm - 1 which is a C - N bond . Based on SEM analysis , the addition of urea have more regular morphology .